For understanding the law of nature - Paradowski, Mariusz (Prawo Kanoniczne, 2023)
This paper concerns multifaceted understanding the law of nature. In the beginning it gives an introduction to the research analysis. Then it presents the paradigm of understanding the law of nature on a historical background. The next part of the elaboration discusses the natural order of things in the philosophy of the ancient Slavs. At the core of their pagan religious practices is a separate paradigm for understanding the importance of the law of nature. The text contains a brief summary.